Valuation-based Accounting Research: Predominance of the Clean Surplus Valuation Model - Djaballah, Abderrahmane (International Journal of Economics and Financial Issues, 2019)
One of the major aims of accounting information is its usefulness in decision-making and in assessing the value of a company. To this end, a vast theoretical and empirical literature has examined the relationship between accounting information and the company’s market value. In this article, we discuss the evolution of this research stream from its origins to the present by outlining the main conclusions. We also review research on the assessment of the company value through accounting determinants. In particular, we examine Ohlson’s Clean Surplus valuation model, discussing its strengths and limitations. The analysis of the conclusions of this research stream provides insights into company valuation through accounting data that are likely to be useful to financial market participants and accounting standard setters. Keywords: Value; Accounting information; Equity valuation; Clean Surplus JEL Classifications: M41; G14 DOI: https://doi.org/10.32479/ijefi.7548